Current energy resources in Kazakhstan and the future potential of renewables: a review - Karatayev, Marat; Clarke, Michèle L. (Elsevier, 2014)
Kazakhstan is rich in natural resources including coal, oil, natural gas and uranium and has significant renewable potential from wind, solar, hydro and biomass. In spite of this, the country is currently dependent upon fossil fuels for power generation. Coal-fired plants account for 75% of total power generation leading to concerns over greenhouse gas emissions and impacts on human health and the environment. Recent economic growth in Kazakhstan has driven increased demand for energy services making the construction of additional generating capacity increasing necessary for enabling sustained growth. In this context, renewable energy resources are becoming an increasingly attractive option to help bridge the demand-supply gap. Despite significant wind, solar, hydro and biomass potential, these resources have not been sustainably captured and deployed due a range of technical, institutional, social and economic barriers. This article reviews the current energy situation in Kazakhstan including fossil energy and renewable resources and investigates policy drivers for the energy sector. The barriers to adoption of renewables are analysed within the context of national climate and energy goals. Recommendations are presented for the promotion, development and implementation of renewable energy resources in Kazakhstan.